Knowledge Assessment of Bad Habits in Children's Oral Cavity Related to Malocclusion - Syafitri, Fuccy Utamy (Dentistry Faculty, 2023)
Background: Bad oral habits are one of the factors that influence the occurrence of malocclusion. Knowledge and understanding of bad oral habits are needed early on to avoid or reduce the severity of malocclusion. The Covid-19 pandemic has prevented face-to-face education, but this can be overcome by providing online education. Objective: This study aimed to determine the level of knowledge of bad oral habits in elementary school-age children regarding the occurrence of malocclusion through online education. Materials and Methods: This cross-sectional analytic study was conducted on grade 5 students at SD Kartika 1-11 Padang City who met the inclusion and exclusion criteria. The selection of respondents was carried out by using a purposive sampling technique. Education is carried out online with the Zoom application. The stages of the activity consist of filling out the pre-test, educating students, asking questions, and filling out the post-test. Student knowledge was measured using a questionnaire consisting of 10 closed questions with a value of 1 if the answer was correct and a value of 0 if the answer was wrong. The research data were processed using the SPSS statistical application. Results: A significant relationship exists between pre-test and post-test knowledge before the intervention. This proves that there is an increase in students' understanding after being given the intervention. Based on the treatment effectiveness test/gain score results, the result was 0.6. So it can be concluded that the intervention provided has moderate effectiveness. Conclusion: A holistic evaluation of changes in behavior and practices in daily life needs to be done to evaluate the success of educating about bad oral habits that can cause malocclusion as a whole.